P87 Use of pocket-sized HIV testing guideline cards to increase HIV testing in medical inpatients. (18th May 2015) - Oxenham, Chantal; Chakravorty, Mithun; El-Nayal, Ayman; Gupta, Nadi
Abstract : Background/introduction: HIV is a chronic treatable condition with an excellent prognosis. There remains, however, a high morbidity and mortality due to late diagnosis, with approximately 1 in 4 HIV patients unaware of their condition. Healthcare professionals have previously seen many of these patients without the diagnosis being made. Rotherham's HIV prevalence is 1.05 per 1000. Late diagnosis made in 56%. Aim(s)/objectives: To increase HIV testing in general medical inpatients. Methods: We obtained a list of all medical inpatients in March 2014 who had been coded with a condition that should prompt HIV testing in accordance with BHIVA 2008 guidance. We reviewed the number of HIV tests requested on medical inpatients during the 1-month period. In June 2014, we delivered a presentation at the Medical Grand Round and two subsequent teaching sessions for staff on HIV testing. We produced a pocket-sized card for staff to attach to the back of their ID badges listing the indications for testing. We compared the proportion of HIV tests performed before and after this intervention. Results: In March 2014, there were 69 patients with clinical indicators for HIV testing. Of those 32 were tested (46.4%). In June 2014, following the intervention, there were 58 patients with clinical indicators and 40 (69.0%) of those were tested. Discussion/conclusion: Following our educational intervention, almost 70% of patients were tested appropriately representing a 22.6% increase from baseline. We plan to re-measure this at a later date to assess whether this increase in uptake of testing has been sustained.